Synthesis and Characterization of Copper Nanoparticles using Stachytarpheta jamaicensis Leaf Extract as A Bioreductant and Evaluation of its Antibacterial Activity Against Pseudomonas aeruginosa - Neneng Lestari; Suyatno Sutoyo (Prodi Kimia, 2026)
Copper nanoparticles are metal particles with a size range of 1–100 nm that have potential as antibacterial agents. This study aimed to determine the characteristics and antibacterial activity of copper nanoparticles synthesized using Stachytarpheta jamaicensis leaf extract as a bioreductor. The synthesis was carried out using a green synthesis method through the reduction of CuSO₄·5H₂O solution with Stachytarpheta jamaicensis leaf extract. Optimization was performed using a UV-Vis spectrophotometer with variations in the ratio of CuSO₄ to extract from 1:1 to 1:4 and pH variations from 7 to 11. The nanoparticles were characterized using UV-Vis spectrophotometry, FTIR, and PSA, while the antibacterial activity was evaluated using the well diffusion method. The results showed that the optimum conditions were obtained at a ratio of 1:4 and pH 8. The synthesized copper nanoparticles had a particle size of 17.03 nm with a maximum UV-Vis absorption wavelength at 310 nm. The Cu–O functional group was identified at a wavenumber of 598.91 cm⁻¹. The copper nanoparticles exhibited very strong antibacterial activity against Pseudomonas aeruginosa with an inhibition zone diameter of 21.96 mm, indicating their potential as an antibacterial agent.